The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1038/s41597-021-00908-9
|View full text |Cite
|
Sign up to set email alerts
|

The transcriptome of wild-type and immortalized corneal epithelial cells

Abstract: Cellular immortalization enables indefinite expansion of cultured cells. However, the process of cell immortalization sometimes changes the original nature of primary cells. In this study, we performed expression profiling of poly A-tailed RNA from primary and immortalized corneal epithelial cells expressing Simian virus 40 large T antigen (SV40) or the combination of mutant cyclin-dependent kinase 4 (CDK4), cyclin D1, and telomere reverse transcriptase (TERT). Furthermore, we studied the expression profile of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…2B in their paper). Based on a previous study that reported genes that were significantly differentially expressed upon induction of the Large T-antigen (Furuya et al, 2021), we noted that more than half of the signature genes compiled for iOSNs, as well as other cell types from the olfactory epithelium (OE), were significantly impacted. The fact that immortalized OP6 cells nevertheless reliably exhibit phenotypic attributes of an iOSN suggests a robust system of post-transcriptional regulation to stabilize cell identity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…2B in their paper). Based on a previous study that reported genes that were significantly differentially expressed upon induction of the Large T-antigen (Furuya et al, 2021), we noted that more than half of the signature genes compiled for iOSNs, as well as other cell types from the olfactory epithelium (OE), were significantly impacted. The fact that immortalized OP6 cells nevertheless reliably exhibit phenotypic attributes of an iOSN suggests a robust system of post-transcriptional regulation to stabilize cell identity.…”
Section: Resultsmentioning
confidence: 99%
“…We trimmed genes previously shown to be misregulated with Large T-antigen expression (Furuya et al, 2021) from the ranked set of signature genes in each of six different OE cell types (Zunitch et al, 2023). We scored OP6 cells based on the normalized FPKM expression level for the top 250 signature genes in each list weighted for relevance based on their ranked position (see Methods).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3D corneal epithelial permeation model using immortalized human primary corneal epithelial cells (HCE-T cells): (A) Morphologies of wild-type, K4DT, and SV40 immortalized corneal epithelial cells. Reprinted from ref with permission under a Creative Commons License 4.0. Copyright 2021 Springer Nature.…”
Section: In Vitro Reconstructed Corneal Tissue Models To Study Drug P...mentioning
confidence: 99%
“…Thus, it is necessary to find a replacement for SV40T to use in tandem with hTERT. BMI-1 [27,35,37,145,158], cyclin D1, and CDK4R24C (mutant cyclin-dependent kinase 4, which cannot be bound by p16INK4a) [159][160][161][162] can be used for this purpose. Studies have demonstrated that hTERT in combination with BMI-1 as immortogenes are associated with the lowest level of chromosome aberrations among SV40T-, hTERT-, and hTERT-BMI-1-immortalized cells [145].…”
mentioning
confidence: 99%